Regional cooling of the extracorporeal blood circuit: a novel anticoagulation approach for renal replacement therapy? - Kroužecký, Aleš; Chvojka, Jiří; Sýkora, Roman; Raděj, Jaroslav; Karvunidis, Thomas; Novák, Ivan; Růžička, Jiří; Petránková, Zuzana; Beneš, Jiří; Bolek, Lukáš; Matějovič, Martin (Intensive care medicine, 2009)
OBJECTIVE: To test the hypothesis that cooling of blood in the extracorporeal circuit of continuous veno-venous hemofiltration (CVVH) enables to realize the procedure without the need of anticoagulation. DESIGN: Experimental animal study. METHODS: We developed the device for selective cooling of extracorporeal circuit (20 degrees C) allowing blood rewarming (38 degrees C) just before returning into the body. Twelve anesthetized and ventilated pigs were randomized to receive either 6 h of CVVH with application of this device (COOL; n = 6) or without it (CONTR; n = 6). MEASUREMENTS: Before the procedure and in 15, 60, 180, 360 min after starting hemofiltration variables related to: (1) circuit patency [time to clotting (TC), number of alarm-triggered pump stopping (AS), venous and transmembranous circuit pressures (VP, TMP)], (2) coagulation status in the extracorporeal circuit [thrombin-antithrombin complexes (TAT(circ)), thromboelastography (TEG)] and (3) animal status (hemodynamics, hemolysis and biochemistry) were assessed. RESULTS: The patency of all circuits treated with selective cooling was well maintained within the observation period. By contrast, five of six sessions were prematurely clotted in the untreated group. As a result, the number of AS was significantly higher in the CONTR group. In-circuit thrombus generation in CONTR group was associated with a markedly increasing TAT(circ). TEG performed at 180 min of the procedure revealed a tendency to a prolonged initial clotting time and a significant decrease in clotting rate of in-circuit blood in the COOL group. No signs of repeated cooling/rewarming-induced hemolysis were observed in animals treated with "hypothermic circuit" CVVH. CONCLUSION: In this porcine model, regional extracorporeal blood cooling proved effective in preventing in-circuit clotting without the need to use any other anticoagulant.
Keywords: Disease Models, Animal; hemofiltrace; prasata; Renal Insufficiency; Swine; Acute Kidney Injury; modely nemocí na zvířatech; terapeutická hypotermie; trombocytóza; renální insuficience; Thrombocytosis; mimotělní oběh; Animals; Hemofiltration; Hypothermia, Induced; Extracorporeal Circulation; zvířata; akutní poškození ledvin